SISTEM SANITASI LINGKUNGAN DI KELURAHAN TANAH GARAM KECAMATAN LUBUK SIKARAH KOTA SOLOK - Tri Agustia (JURNAL BUANA, 2021)
This study aims to determine: 1) The condition of the drainage system in Tanah Garam Village, Lubuk Sikarah District, Solok City 2) Household waste management in Tanah Garam Village, Lubuk Sikarah District, Solok City 3) Provision of healthy latrines in Tanah Garam Village, Lubuk Sikarah District, Solok City. This type of research is classified as a descriptive study with a quantitative approach.Data collection using a questionnaire, as well as for data management using percentage analysis. The results of this study are: 1) The condition of the drainage channel in Tanah Garam Village, Lubuk Sikarah district, Solok City is still classified as bad, as evidenced by the data collected in the average field. On average, respondents think that the drainage channel is still bad because the flow of the drainage channel is often flooded and overflows which can cause disease nests 2) Household waste management in Tanah Garam Village, Lubuk Sikarah District, Solok City is still classified as bad because there are still many people who are found burning rubbish and carrying out landfills when disposing of garbage to TPS (landfills) and awareness of waste separation 3) The availability of healthy latrines in the Salt Land Family is also categorized as low, this is evidenced by the fact that there are still people who have not provided healthy latrines in their respective homes and there are also people who I take a shower and wash toilets on the banks of the river